NSW DICE forum and training: conference review - Yvonne Hughes (Scottish Journal of Residential Child Care)
The Australian Disrupting Child Sexual Exploitation (DICE) project aims to address the need for further development of multiagency prevention and disruption approaches to child sexual exploitation (CSE) to better safeguard children in residential out-of-home-care settings. The tri-state project is led by Professor Cathy Humphreys and Dr Gemma McKibbin and takes place across sites in New South Wales (NSW), Victoria and Queensland. The NSW chapter is led by Chief Investigator Professor Susan Heward-Belle and is supported by NSW partner agencies – including MacKillop Family Services, Department of Communities and Justice (DCJ), NSW Police, The University of Sydney, and the Australian Centre to Counter Child Exploitation (ACCCE).